The Effect of Labor Flexibility on Firm Performance in Indonesian Telecommunication Industry - Natasaputra, Nugraha; Kusumastuti, Ratih Dyah (International Research Journal of Business Studies, 2014)
The purpose of this study is to analyze the influence of the dynamic business environment, the type of the company’s business strategy external labor flexibility, and internal labor flexibility on the firm performance. The unit of analysis in this study is the company, i.e. the companies in the telecommunications sector in Indonesia. This study uses primary data, through the distribution of questionnaires. Statistical technique used is partial least squares structural equation method (PLS-SEM). The findings suggest that the implementation of labor flexibility is important for the company to compete more efficiently in the market, but the implementation should match the company’s goal. Moreover, to achive the best firm performance, the company may implement both types of labor flexibility, however the implementation of internal labor flexibility should have higher priority.